Molecular biology of the cell - Alberts, Bruce; Morgan, David; Heald, Rebecca; Johnson, Alexander; Raff, Martin; Roberts, Keith; Walter, Peter (W. W. Norton & Company, 2022)
"As the amount of information in biology expands dramatically, it becomes increasingly important for textbooks to distill this vast amount of scientific knowledge into concise principles and enduring concepts. Molecular Biology of the Cell, Seventh Edition accomplishes this goal with clear writing and beautiful illustrations. The Seventh Edition has been extensively revised and updated with the latest research in cell biology, and it provides an exceptional framework for teaching and learning. Molecular Biology of the Cell is widely used in introductory courses at the university level, being considered as a reference in many libraries and laboratories around the world. It describes the current understanding of cell biology and includes basic biochemistry, experimental methods for investigating cells, the properties common to most eukaryotic cells, the expression and transmission of genetic information, the internal organization of cells, and the behavior of cells in multicellular organisms. Molecular Biology of the Cell has been described as "the most influential cell biology textbook of its time""--